2008
DOI: 10.5194/acp-8-1483-2008
|View full text |Cite
|
Sign up to set email alerts
|

Validation of ACE-FTS satellite data in the upper troposphere/lower stratosphere (UTLS) using non-coincident measurements

Abstract: Abstract. CO, O 3 , and H 2 O data in the upper troposphere/lower stratosphere (UTLS) measured by the Atmospheric Chemistry Experiment Fourier Transform Spectrometer (ACE-FTS) on Canada's SCISAT-1 satellite are validated using aircraft and ozonesonde measurements. In the UTLS, validation of chemical trace gas measurements is a challenging task due to small-scale variability in the tracer fields, strong gradients of the tracers across the tropopause, and scarcity of measurements suitable for validation purpose… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(105 citation statements)
references
References 33 publications
8
97
0
Order By: Relevance
“…All reanalyses contain high biases relative to the SDI MIM at pressures greater than 100 hPa (see also Jiang et al, 2015), although this may in part be explained by the increase in measurement uncertainty of satellite limb sounders with decreasing altitude in the upper troposphere . Several studies have shown that Aura MLS contains a dry bias in the upper troposphere/lower stratosphere around 200 hPa (e.g., Davis et al, 2016;Vömel et al, 2007), and similarly a dry bias has been found in the upper troposphere for ACE-FTS (Hegglin et al, 2008). The comparisons in Fig.…”
Section: Zonal Mean Water Vapor Cross Sectionsmentioning
confidence: 71%
“…All reanalyses contain high biases relative to the SDI MIM at pressures greater than 100 hPa (see also Jiang et al, 2015), although this may in part be explained by the increase in measurement uncertainty of satellite limb sounders with decreasing altitude in the upper troposphere . Several studies have shown that Aura MLS contains a dry bias in the upper troposphere/lower stratosphere around 200 hPa (e.g., Davis et al, 2016;Vömel et al, 2007), and similarly a dry bias has been found in the upper troposphere for ACE-FTS (Hegglin et al, 2008). The comparisons in Fig.…”
Section: Zonal Mean Water Vapor Cross Sectionsmentioning
confidence: 71%
“…However, atmospheric features may also be captured by only one of the two instruments not only because of different sampling in the horizontal, but also because of vertical sampling and resolution differences. ACE-FTS has been shown to often achieve an effective vertical resolution near 1 km in the UTLS (Hegglin et al, 2008); while the ability of MLS to resolve smallvertical-scale features has yet to be explored in detail, Fig. 9 and the accompanying discussion suggest that it does capture variability on scales that might not be obvious given the nominal resolution.…”
Section: Trace Gas Measurements In Jet Coordinatesmentioning
confidence: 99%
“…We use version 2.2 of the ACE-FTS ozone data. Hegglin et al (2008) found that the version 2.2 ACE-FTS profiles have an effective vertical resolution of 1 km in the UTLS. Validation of the ACE-FTS O 3 data suggested that the relative mean difference between ACE-FTS O 3 data and independent measurements is less than 8 % between 16-44 km.…”
Section: Data Setsmentioning
confidence: 99%
“…Validation of the ACE-FTS O 3 data suggested that the relative mean difference between ACE-FTS O 3 data and independent measurements is less than 8 % between 16-44 km. Hegglin et al (2008) evaluated the data in the UTLS and reported mean differences relative to aircraft and ozonesonde data of about 8 % in the lower stratosphere and a high bias of 18 % in the upper troposphere. We restrict our use of the ACE-FTS data to the lower stratosphere.…”
Section: Data Setsmentioning
confidence: 99%